Hydrogen production and metabolic response of Spirulina sp , Calothrix parteniana and Oscillatoria sp to sulphur and /or nitrogen deficiency - F.Hifney, Awatief; Abdel-Basset, Refat (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
Spirulina platensis SAG obtained from (Sammlung von Algen culturing Gottingen), Calothrix parteniana and Oscillatoria sp. (isolated from Egyptian soil sample) were cultivated in BG11 medium either in the presence of nitrogen and sulphur (control culture condition) or without addition of nitrogen (N0) or sulphur (S0) and combined nitrogen and sulphur (N0S0) source to detect the effect of these element limitation on growth and hydrogen production of the tested algal isolates . The growth expressed as dry weight and chlorophyll content was generally inhibited in treated culture sample (N0 and /or S0) of all sp under study. Photosynthetic O2 evolution expressed as µ mol O2†‘/mg Chll.a/h. of Spirulina sp and Calothrix parteniana,Oscillatoria sp were severely dropped under nitrogen deficiency compared with control and sulphur limited growth condition. Respiratory oxygen uptake was however, increased with the above deficiency effect in all investigated spp. Assay of Hydrogen production using hydrogen electrode (expressed as nmol H2†‘/mg.chla/h) revealed that nitrogen or sulphur deficiency growth condition stimulated hydrogen production in all isolate under testing. Combination of both element deficiencies has an inhibition effect on hydrogen yield in Calothrix parteniana and Oscillatoria sp. Amazingly our results indicate that Spirulina sp was the only culture able to produce hydrogen in combined nitrogen and sulphur deficiency growth condition, Spirulina produce hydrogen in dark condition only, while the presence of light was very important for hydrogen production in other investigated cyanobacterial cultures. The above effect of nitrogen and sulphur deficiency demonstrate that both elements play a crucial role in growth and metabolism especially hydrogen production.